Projeto de um centro de jogos virtuais em Belém-PA - TEIXEIRA, Sonia da Silva (2023)
This paper deals with a design proposal of a Virtual Games Center in the city of BelémPA. The proposal is for a building that is a technological cultural center focused on electronic games, popularly known as video games. The premise that guided the proposal was to create spaces that considers the specificity of the equipment that the room will host, so that the user can enjoy the experience with convenience. The work is structured in 1 chapter of reference projects, 1 of characterization of the study area, 1 of pre-project and 1 of project proposal.